Analisis SWOT Sebagai Dasar Perencanaan Strategi Pemasaran Pada Agrowisata Belimbing Karangsari Kota Blitar - Rizky Kurniawati; Novi Marlena (Universitas Muhammadiyah Jember, 2020)
Karangsari starfruit agrotourism is one of the agriculture-based tourism attraction established by the Blitar City government and managed by Karangsari Village’s residents. Karangsari Starfruit Agrotourism was established with the aim of developing the region's potential through the development of tourism objects in order to be able to develop and improve the welfare of the surrounding community economically. This type of research is a qualitative study with managers and employees of Karangsari starfruit agrotourism as the research subject. This study uses 4 (four) stages of data analysis that is, namely the first stage data collection using interviews, observation and documentation with internal factors (strengths-weaknesses) and external factors (opportunities-threats) as data acquisition, then the second stage the data of reduction stage uses EFE and IFE matrix with the results of calculations including strength’s score is 1.66; weakness’ score is 0.89; opportunity’s score is 1.98; threat’s score is 0.51. Then the third stage of data display stage uses the SWOT Matrix which the result of alternative strategy is SO (Strength-Opportunity). The last one is drawing conclusions that produce alternative strategy recommendations for Karangsari Starfruit Agrotourism, including the use of technology and cooperation with various parties such as travel agents